INFLUENCE OF PRODUCT QUALITY, PRICING AND DISTRIBUTION CHANNELS ON CONSUMER PURCHASE DECISIONS AT PT. METRO ARTHA PRAKARSA - Jimmy Halim; Ricardo Hua; Andree Felix; Hartono Salim (Jurnal Mantik, 2022)
Product quality, pricing and distribution channels are elements that can influence purchasing decisions. This study aims to determine and analyze the effect of product quality, pricing and distribution channels on consumer purchasing decisions at PT. Metro Artha Prakarsa. This type of research is explanatory research. The entire population is the average daily consumer who makes repeat purchases at the company totaling 189 consumers. Due to the large number of populations, the sampling technique will be reduced by using the Slovin formula for an error tolerance level of 5% so that 128 respondents are obtained in the study which will be divided into questionnaires as measured by a Likert scale. Data analysis used multiple linear regression analysis and coefficient of determination as well as simultaneous and partial tests. The results showed that either partially or simultaneously, product quality, pricing, and distribution channels had a positive and significant impact on consumer purchasing decisions at PT. Metro Artha Prakarsa. Based on the results of this study, the implications for management are to make more improvements to product quality so that it can be better, provide attractive price offers and maximize distribution.